An Efficient Operator-Splitting Method for Noise Removal in Images (Communications in Computational Physics, 2006)
In this work, noise removal in digital images is investigated. The importanceof this problem lies in the fact that removal of noise is a necessary pre-processing stepfor other image processing tasks such as edge detection, image segmentation, imagecompression, classification problems, image registration etc. A number of differentapproaches have been proposed in the literature. In this work, a non-linear PDE-basedalgorithm is developed based on the ideas proposed by Lysaker, Osher and Tai [IEEETrans. Image Process., 13 (2004), 1345-1357] . This algorithm consists of two steps: flowfield smoothing of the normal vectors, followed by image reconstruction. We proposea finite-difference based additive operator-splitting method that allows for much largertime-steps. This results in an efficient method for noise-removal that is shown to havegood visual results. The energy is studied as an objective measure of the algorithmperformance.